HUBUNGAN PERILAKU LANSIA DAN DUKUNGAN KELUARGA TERHADAP PEMANFAATAN POSYANDU LANSIA DI WILAYAH KERJA PUSKESMAS DARUSSALAM TAHUN 2012 - fitri Hayani; Namora Lumongga; Tukiman . (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
ABSTRACT One of the successes of development in the health sector is growing Life expectancy (UHH) which is a leading indicator of the health of public health. To achieve health care efforts at the community level that The Integrated Service for old-agers. This research is an analytic survey with cross sectional study design, which is to portray how the relationship behavior of elderly and family support for the the service for old-agers utilization. The population of this study were all elderly aged ≥60 years with as many as 1420 people in the work area Darussalam health center with a simple random sampling as many as 96 person. The data used are primary through interviews and secondary data, the data were analyzed using chi-square test. The results showed that there was relation between knowledge with the use of the service for old-agers ((p)=0.001), there was relation between attitude with the use of the service for old-agers ((p)=0.001), there was relation a family support is informational support the family ((p)=0.001), support a family assessment ((p)=0.001), family instrumental support ((p)=0.003) and emotional support to the family ((p)=0.001) with the use of the service for old-agers. For agencies, health center and village are advised to increase outreach to the elderly and elderly families (General Discussion Elderly/BKL) involves a variety of activities and objectives are implemented the service for old-agers the health centers health center so hopefully would utilize the service for old-agers elderly. Keywords: elderly behavior, family support, use of the service for old-agers.